Identification of Factors that Influence Exclusive Breastfeeding during the Covid-19 Pandemic : Identifikasi Faktor yang Mempengaruhi Pemberian ASI Eksklusif selama Pandemi Covid-19 - Zulaida, Iid Putri; Nawangsari, Harnanik; Arham, Afif Hidayatul (Universitas Muhammadiyah Sidoarjo, 2022)
The Covid-19 pandemic has a major impact on exclusive breastfeeding. The aims of the study was to identify factors that influence exclusive breastfeeding during the Covid-19 pandemic based on empirical studies of the last 2 years. The research design uses a literature review. The data source uses Elsevier, BMC, and Scholar databases with topics published in Indonesian and English for 2 years (2020–2021). The review method uses journal searches according to the PICOS framework with keywords that match the writing. Journals are selected by journal selection and abstracts with inclusion and exclusion criteria so that journals are found that can be reviewed. The results of the study stated that the role of breastfeeding counselors, knowledge, psychology, family support, lockdown, and rooming in, family resilience, breastfeeding experience, maternal health status, and promotion of formula milk influenced exclusive breastfeeding. Based on the results of the study, it was found that the factors that influence exclusive breastfeeding during the Covid-19 pandemic are the role of counselors, knowledge, psychology, family resilience, rooming in, family support, mother's experience, lockdown, promotion of formula milk, and maternal health conditions based on the last 2-year empirical study.